The Early Diagnosis of Scrub Typhus by Metagenomic Next-Generation Sequencing - Liu, Xianghong; Zhang, Ye; Zhang, Jun; Lou, Zheng; Xia, Han; Lu, Zhijuan (Frontiers in Public Health, 2021)
Introduction: Scrub typhus is a mite-borne infection widespread in Southeast Asia, with clinical symptoms such as fever, chills, skin rash, eschar at the bite site, and other signs of acute febrile illness. The Rickettsia pathogen (Orientia tsutsugamushi) is always difficult to be early diagnosed by traditional clinical diagnostic methods, especially for patients without typical eschar. This greatly increases the mortality of patients with scrub typhus. A new approach should be introduced to improve its clinical diagnosis. Methods: During May 2018 to March 2021, 13 samples from 10 patients with suspected scrub typhus were collected. Metagenomic next-generation sequencing (mNGS) and other clinical methods (including serology, culture, and indirect immunofluorescence test (IIFT)) were used to identify the pathogens in this study. Results: The results of mNGS were all positive, with mapped reads of Orientia tsutsugamushi ranging from 1 to 460. Eight patients (80%) were diagnosed as scrub typhus. The other two were diagnosed as suspect scrub typhus due to the limited number of pathogen reads (one and two, respectively). According to clinical evidences, all patients were finally diagnosed as scrub typhus, except for patient 9 with one unique read diagnosed as acute exacerbation of chronic obstructive pulmonary disease. For the five scrub typhus patients without typical eschar, mNGS gave all positive results (4-460 specific reads). For other methods, only Weil Felix reaction of one patient detected the pathogen. In addition, the respiratory tract profile (IgM) detected various pathogens, but all were confirmed to be false positive. Conclusions: mNGS performed better than conventional clinical methods to early diagnose scrub typhus. This approach can be routinely carried out for early and precise diagnosis in clinical infections, especially for those hard to be identified by traditional diagnostic methods.